Clinical and biochemical characteristics of diabetic ketoacidosis in adults with type 1 or type 2 diabetes at a tertiary hospital in the United Arab Emirates - Almazrouei, Raya; Siddiqua, Amatur Rahman; Alnuaimi, Mouza; Al-Shamsi, Saif; Govender, Romona (Frontiers in Clinical Diabetes and Healthcare, 2022)
Background Diabetes ketoacidosis (DKA) is a well-known acute complication of diabetes. This study aims to describe the sociodemographic, clinical, and biochemical characteristics of adult patients with different diabetes types and DKA severities attending a tertiary hospital in the UAE. Methods We retrospectively extracted sociodemographic, clinical, and laboratory data from the electronic medical records of 220 adult patients with DKA admitted to Tawam Hospital between January 2017 and October 2020. Results The average age was 30.6 ± 16.6 years of whom 54.5% were women, 77.7% were UAE nationals and 77.9% were Type 1 diabetes (T1DM). 12.7% were newly diagnosed with diabetes. Treatment noncompliance (31.4%), and infection (26.4%) were the main precipitating factors. Most patients presented with moderate DKA (50.9%). Compared to T1DM, patients with Type 2 diabetes (T2DM) were older (53.6 vs 23.9 years, p < 0.001), had longer hospital stay (12.1 days vs 4.1 days, p < 0.001), had more complications (52.1%, vs 18.9% p <0.001), and a higher mortality rate (6.3% vs 0.6%, p = 0.035). Patients with severe DKA had a shorter diabetes duration compared to mild and moderate DKA (5.7 vs 11.0 vs 11.7 years, respectively, p = 0.007), while complications were significantly lower in the mild group compared to both the moderate and severe groups (11.6% vs 32.1% vs 33.3%, respectively). Conclusion The risk of DKA is higher for patients with T1DM than for those with T2DM. The clinical characteristics and outcomes of patients with T2DM differ from those with T1DM highlighting the importance of educating all patients about DKA.